CUMHURİYET TAŞRASINDAN BİR KESİT: MUŞ [1925-1938] - Çağlayan, Ercan (My University, 2016)
Cumhuriyet'in kuruluşunda bir vilayet statüsünde olan Muş, 1925 Şeyh Said Ayaklanması'nın hemen akabinde kazaya dönüştürülerek Bitlis vilayetine bağlandı. 1929 yılında çıkarılan bir kanunla Muş adıyla yeni bir vilayet kuruldu ve aynı kanunla Bitlis vilayeti Muş vilayetine bağlı bir kazaya dönüştürüldü. 1936 yılında Muş vilayetine bağlı Çapakçur [Bingöl] ve Bitlis kazalarının vilayet yapılmasıyla Muş vilayetinin erken Cumhuriyet dönemindeki idari sınırları çizilmiş oldu.Bu idari düzenlemelerin yanı sıra, tüm ülke için olduğu gibi Muş için de 1930'lu yıllar, Kemalist rejimin belirlediği değişikliklerin ve uygulamaların gerçekleştiği yıllar olmuştur. Muş, 1930'lu yıllarda bir taraftan Kemalist ilkeler doğrultusunda imar ve inşa edilirken diğer taraftan Halkevinin bilhassa sosyal ve siyasal faaliyetleriyle yeni bir imaja büründürülmeye çalışılıyordu. Bu sınırlı çalışma, 1925-1938 yılları arasındaki dönemde Muş vilayetini konu edinmektedir. İki bölümden oluşan çalışmanın birinci bölümünde söz konusu dönemde Muş'un idari yapısındaki değişiklikler ve "modern" mimari ölçütlerince yeniden imarı, ikinci bölümde ise Muş Halkevi'nin faaliyetleri ele alınmaktadır.

Muş had a province status during the establishment of the Turkish Republic but immediately after the Sheikh Said Revolt in 1925 its status was changed into a small township and Muş became a town of Bitlis province. By making a law in 1929, a new province named Muş was established and with the same law Bitlis became a town of the new Muş province. When the status of çapakçur [Bingöl] and Bitlis towns, which were two towns of Muş province, was changed into a province in 1936, the administrative borders of Muş province in the early Republican era became clear. In addition to these administrative arrangements, not only for Muş but also for the whole country1930s became the period when the changes and applications that the Kemalist regime made were performed. In 1930s on the one hand Muş was constructed and reconstructed in accordance with the Kemalist principles, and on the other hand its image was being changed by the social and political activities of the People's House (Halkevi). The current limited study focuses on Muş province between the years of 19251938, the period called as early Republican era. The study has two sections; the first one investigates the changes taking place in the administrative structure of Muş and its reconstruction according to the 'modern' architectural standards, while the second section covers the activities of People's House in Muş.
A SECTION ON A REPUBLICAN TOWN: MUŞ [1925-1938]